Foreign Direct Investment in Indonesia: Implications of Real Minimum Wages, Economic Growth, and Perceptions of Corruption (2003–2023) - Pramudya Darel Sitorus; Any Widayatsari; Darmayuda Darmayuda (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Foreign direct investment plays an important role as a catalyst for the Indonesian economy in realizing the golden Indonesia 2045, especially in increasing capital inflows, creating jobs, improving infrastructure and transferring technology and knowledge. The purpose of this study is to determine the effect of real minimum wage, economic growth and corruption perception index on the inflow of foreign direct investment in Indonesia in the period 2003 - 2023. The research method used is multiple regression analysis method (ordinary least square) using eviews 12. Data was collected through the Central Bureau of Statistics, Investment Coordinating Board, One Data Ministry of Manpower, and Transparency International. The results of this study show that partially, real minimum wage and economic growth have a positive effect on foreign direct investment, while corruption perception index has no effect on foreign direct investment. Furthermore, simultaneously real minimum wage, economic growth and corruption perception index affect foreign direct investment with 5% significance degree.